Dual perspectives on learning analytics in higher education - Parrish, Andrea Harkins; Richman, Laila J (Journal of applied research in higher education, 2020)
Purpose In higher education, the authors serve multiple stakeholders with varying perspectives on the institution’s learning analytic system. The purpose of this paper is to highlight dual perspectives within the learning analytics (LA) system in one institution: that of an administrator responsible for college-wide improvement, and a faculty member responsible for programmatic improvement. Design/methodology/approach This manuscript provides a critical perspective with dual sets of experiences and viewpoints. This approach allows close examination of each perspective within the context of the existing literature, as the authors examine transitions in the use of LA. Findings These viewpoints offer insight into the interpretation of LA through the lens of various roles. In examining these viewpoints, the authors offer three actionable steps for other institutions who seek to implement. Practical implications These actionable steps offer a starting point for other institutions to engage in conversations related to the adoption of LA for continuous improvement across levels and roles. Relevant implications for various parties are discussed, with an emphasis on how administrators within the university system may support faculty to incorporate LA as part of their scholarly and teaching responsibilities. Originality/value Few studies have examined the perspectives of multiple stakeholders within an institution. Here the authors have presented these dual perspectives in order to further the dialogue between university administration and faculty as analytic systems become more widespread. Through this dialogue, the authors see increased opportunities for all stakeholders to better understand their role in LA.